Well-Being and Cooking Behavior: Using the Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment (PERMA) Model as a Theoretical Framework - Farmer, Nicole; Cotter, Elizabeth W. (Frontiers in Psychology, 2021)
The prevalence of psychosocial distress is increasing in the United States. At the same time, the American default lifestyle has steadily displaced household food production with industrial food production, despite increased cultural interest in cooking. An important focus of cooking research to date has been on cooking’s association with nutrition and dietary quality. Less focus has been placed on how cooking might foster the qualities that allow for mitigation of psychosocial distress and promote well-being. Rooted in its evolutionary role in the human experience, cooking requires skills and knowledge that have the capacity to encourage aspects of well-being as described by Seligman as flourishing. Evidence for a beneficial role of cooking in psychosocial health exists, but the exploration is limited, potentially due to lack of a theoretical context to explain these benefits. From this perspective, we review the current literature showing the application of Seligman’s prominent well-being model, PERMA (Positive emotion, Engagement, Relationships, Meaning, Accomplishments), to cooking, defined as the activity related to the preparation of food or a meal. We propose that the PERMA model as applied to cooking may function as a theoretical framework to explore psychosocial outcomes associated with cooking. Broader application of this approach may also help to further the application of positive psychology in the developing literature around psychosocial health and nutrition-related chronic diseases.